Treatment and care for young amphetamine-type stimulant users - Bruun, A.; Ennis, D.; Wansbrough, H.; Green, Rachael; Mitchell, P. (IP Communications, 2012)
In the early to mid-2000s, researchers, policy-makers, and service providers began to respond to a dramatic increase in the prevalence of crystal methamphetamine use in the community (McKetin & McLaren 2004). The Australian media touted such trends as indicative of an 'epidemic' termed the 'ice age' (Carney 2006); however, more recent data indicate that rates of use may have declined. For example, an annual survey of Australian regular ecstasy users in 2007 found that 71 % of the sample had used any type of methamphetamine in the previous six months, compared to 54% in 2009 (Black et al 2008; Sindicich & Burns 2010). Despite this drop, methamphetamine continues to be one of the most commonly used illicit drugs among young people in our community (Cassar et al 2009; Sindicich & Burns 2010). In this chapter we investigate how service providers and practitioners can best respond to the particular needs of those young people whose use of amphetamine-type stimulants (ATS), particularly methamphetamine, has become dependent and problematic.